Actinomyces naeslundii causing pulmonary endobronchial Actinomycosis - A case report - B G Supriya; S Harisree; Jayanthi Savio; Priya Ramachandran (Wolters Kluwer Medknow Publications, 2019)
Actinomyces naeslundii is a commensal flora of the oral cavity and is generally considered as an avirulent saprophytic bacterium in immunocompetent patients. It can become an opportunistic anaerobic pathogen in oral cavity in patients with poor oral hygiene or tooth extraction and can cause periodontal disease. Pulmonary Actinomycosis is a rare manifestation and may be suspected in middle-aged male patients with cough and hemoptysis showing radiological findings of a peripheral mass or chronic consolidation in whom repeated aerobic cultures have yielded negative results. Here, we report isolation of A. naeslundii from the bronchoalveolar lavage sample from an immunocompetent patient who presented with chronic nonresolving pneumonia of 6 months duration.